A truly testing experience – how Model Based Systems Engineering can help to ensure that you build the right product and build the product right. Issue 1 (13th September 2016) - Wilson‐Smith, Mike; Kibler, Anna
Abstract: Model Based Systems Engineering (MBSE) tends to be very focused on the early system lifecycle stages (the "left side of the Vee" in a traditional, sequential lifecycle model) which, whilst understandable, can mean that some of the benefits of MBSE are not fully flowed through to the Verification and Validation (V&V) stages of the lifecycle. The goal of this paper is to illustrate how an MBSE approach and associated methods can be used to influence and guide the V&V of systems and the Systems of Systems (SoS) that are formed from the interoperation of these systems. The approaches and methods illustrated have been applied in both the development of naval platforms (or systems) and the interoperation of these platforms via military communications with other platforms across multiple domains (air, sea and land).